PENGARUH PENDIDIKAN KESEHATAN TERHADAP KEPATUHAN DIET PADA PENDERITA HIPERTENSI - Kurniawati Kurniawati; Wiwiek Widiatie (Universitas Muhammadiyah Jember, 2017)
Hypertension, where the patient blood pressure is above normal. One of the compliance to obey by hypertensive patients is food (dietary compliance). Dietary is one of the methods to reduce the complication at hypertensive patients. This research aimed at finding out the influence of health education against the compliance. This research was pre-experiment by applying one group pre-post test design. The populations were hypertensive patient at the country of Tambar, Jombang. The samples were 30 respondents the patients who fulfill the criteria. This also used systematic simple random sampling technique. Giving a questionnaire was a data collection before the health education run. Then, it continued with health education about dietary for hypertensive. A week after the education run, the patients had to fill the questionnaire to investigate the compliance. The analysis used Wilcoxon Signed rank Test, significance level was ρ0.05.The result was 0,000 which mean that health education influenced dietary compliance for hypertensive patient. This is therefore health education should be implemented regularly in period of time to adapt with patient by applying well communication.